Kinetically decoupled electrical and structural phase transitions in VO₂ - Sahu, S.R. (2023)
Vanadium dioxide (VO2) has drawn significant attention for its near room temperature insulator to metal transition and associated structural phase transition. The underlying Physics behind the temperature induced insulator to metal and concomitant structural phase transition in VO2 is yet to be fully understood. We have investigated the kinetics of the above phase transition behaviors of VO2 with the help of resistivity measurements and Raman spectroscopy. Resistance thermal hysteresis scaling and relaxation measurements across the temperature induced insulator to metal transition reveal the unusual behaviour of this first-order phase transition, whereas Raman relaxation measurements show that the temperature induced structural phase transition in VO2 follows usual behaviour and is consistent with mean field prediction. At higher temperature sweeping rates decoupling of insulator to metal transition and structural phase transition have been confirmed. The observed anomalous first order phase transition behavior in VO2 is attributed to the unconventional quasi particle dynamics, i.e. significantly lowered electronic thermal conductivity across insulator to metal transition, which is confirmed by ultrafast optical pump-probe time domain thermoreflectance measurements.